"The hook‐up": How youth‐serving organizations facilitate network‐based social capital for urban youth of color. Issue 7 (24th June 2019) - Dill, LeConté J.; Ozer, Emily J.
Abstract: Young people of color residing in distressed urban contexts face challenges in accessing social capital that supports positive development and the transition to educational and employment opportunities. Youth‐serving organizations play potentially important roles for youth participants to access and leverage networks. This ethnographic study draws on qualitative interviews, conducted with adolescents at a youth‐serving organization based in East Oakland, California, to examine how network‐based social capital is activated and sustained for and by urban Black and Latinx youth. We found that relationships with supportive adult staff at the organization put youth in contact with caring, trusted adults of color outside of their families who serve as role models for them. These adults provide loving accountability to young people, serving as critical forces in distressed and stigmatized communities. We also found that adult staff activate social leverage to garner various current and future educational and professional opportunities for the youth there. These unique opportunities serve to boost young people's current self‐esteem and also to prime them to envision positive futures for themselves. Overall, these findings point to the importance of interpersonal pathways embedded within neighborhood institutions in the activation of network‐based social capital.